(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Object Of This Study Is To Find Out The Impact Of Social Responsibility Costs On Corporate Performance, Which Today Relies On A Three-Pronged Policy, It Attempts To Reflect A Complex Understanding Of Social And Environmental Performance As Well As Financial Performance These Companies Adopt Social Responsibility Towards Employees, Society And The Environment, Giving Them Greater Opportunities To Develop Their Performance,So The Costs Of This Responsibility According To Many Studies Would Give It A Positive Advantage ,Increase Its Financial Performance And Offer It Opportunities To Invest In Long Terms; Although There Is A Problem In The Classification And Measurement Of These Costs In Short Terms. Keywords: Social Responsibility, Social And Economic Costs, Financial Performance.